2016
DOI: 10.3892/ijmm.2016.2718
|View full text |Cite
|
Sign up to set email alerts
|

Low vitamin D-modulated calcium-regulating proteins in psoriasis vulgaris plaques: S100A7 overexpression depends on joint involvement

Abstract: Psoriasis is an inflammatory skin disease with or without joint involvement. In this disease, the thickened epidermis and impaired barrier are associated with altered calcium gradients. Calcium and vitamin D are known to play important roles in keratinocyte differentiation and bone metabolism. Intracellular calcium is regulated by calcium-sensing receptor (CASR), calcium release-activated calcium modulator (ORAI) and stromal interaction molecule (STIM). Other proteins modulated by vitamin D play important role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 86 publications
0
19
0
Order By: Relevance
“…Previous reports have indicated that STIM1 has no apparent role in normal ASMCs [7], but recent microarray analysis of clinical samples has provided intriguing evidence that STIM1 may be a factor in AMD [8]. Evidence suggests that vitamin D deficiency suppresses the expression of a number of calcium-regulating proteins, including STIM1 [9,10]. As is well known, AMD is closely related to the process of ageing.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have indicated that STIM1 has no apparent role in normal ASMCs [7], but recent microarray analysis of clinical samples has provided intriguing evidence that STIM1 may be a factor in AMD [8]. Evidence suggests that vitamin D deficiency suppresses the expression of a number of calcium-regulating proteins, including STIM1 [9,10]. As is well known, AMD is closely related to the process of ageing.…”
Section: Introductionmentioning
confidence: 99%
“…These immune-related molecules play an important role in the regulation of osteoblast and osteoclast differentiation. S100A7 promotes osteoclast differentiation and activity by enhancing the effects of M-CSF and RANKL [34][35][36] . However, several other factors effectively promote the proliferation and differentiation of osteoblasts and bone formation while inhibiting bone resorption [37][38][39][40][41][42][43][44] .…”
Section: Discussionmentioning
confidence: 99%
“…A homolog of psoriasin, a common protein in psoriasis patients, was identified in bovines and had the same antimicrobial and immune response activity as the human protein 44 . Further, Ca and vitamin D play important roles in keratinocyte differentiation and regulate proteins involved in psoriasis 45 and S is used as a known treatment and prevention of recurrence for this disease 46 . Our results suggest the genes whose expressions were correlated to bta-miR-369-3p expression as new candidate targets of this miRNA, linked to immune response and mineral concentration.…”
Section: Discussionmentioning
confidence: 99%